Social commerce in e-business of Pakistan: opportunities, challenges and solutions - Solangi, Yasir Ali; Solangi, Zulfiqar Ali; Raza, Ali; S. Abd. Aziz, Madihah; Hamzah, Mohd Syarqawy; Shah, Asadullah (IEEE Explore, 2018)
social media make ultimate building blocks in the development of novel approaches in e-business of Pakistan with the conjuncture of Web 2.0 social media has a variety of application domain including social commerce. S-commerce is redesigning modern e-business with promising economic technological and social outcrop. Customers keep their expectations higher always, so precisely all business are trying to exceed the customers' expectations with pre and post-sale interaction on social networking sites like face book or Twitter accounts. Customers can interact, look and compare company products, reviews and feedback in their social circle friends of friends of friends. This paper proposes a survey about prospects of social commerce in e-business of Pakistan. In addition, this paper would proposes research framework for foster future e-business opportunities, challenges and provide a solution to build up buyers trust as well as to enhance the interactive online buying process in local e-business of Pakistan using social media.